(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2025)
In its first Dossier entirely dedicated to the world of stage characterization, the magazine A Luz em Cena represents the professionals in the field on its cover with the work of the characterization artist Cleber de Oliveira for the show O Mundo de Hundertwasser. Cleber’s work not only brings the technical quality of an excellent characterization project, but also poetically summarizes the combination of practical elements of daily work with symbolic elements of becoming a professional throughout life and experiences.